Pathophysiological mechanism of worsened clinical outcome by lowered left ventricular cardiac power output in heart failure. (4th February 2022) - Aoyagi, H; Tsujinaga, S; Iwano, H; Ishizaka, S; Tamaki, Y; Motoi, K; Chiba, Y; Murayama, M; Nakabachi, M; Nishino, H; Yokoyama, S; Sato, T; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiac power output (CPO) is a measure of cardiac pumping function, and CPO during exercise is known to be a powerful prognostic marker of heart failure. Despite its prognostic significance, pathophysiological mechanism of the association between reduced CPO and worse clinical outcome is unknown. We hypothesized that reduced CPO is associated with worse outcome through the reduced exercise capacity and enhanced ventilatory response. Methods: Cardiopulmonary exercise testing and exercise stress echocardiography were performed in consecutive 64 patients with chronic heart failure who admitted to our department for the management of heart failure [60 ± 14 years old, left ventricular (LV) ejection fraction 39 ± 16%, ischemic etiology 16%, brain natriuretic peptide 124 pg/ml (51-313)]. Peak oxygen uptake (peak VO2) and the lowest minute ventilation / carbon dioxide production ratio (VE/VCO2) were measured as a parameter of exercise tolerance and that of ventilatory response, respectively. LV ejection fraction was measured by disk summation method at peak exercise. By using Doppler images, E/e" at peak exercise was measured as a marker of LV filling pressure, and CPO normalized by LV mass was obtained as 0.222 × cardiac output × mean blood pressure / LV mass [W/100 g]. Cardiac events defined as hospitalization for heart failure, cardiac death, or implantation of a LV assist device after the examinations were recorded. Results: CPO at rest was weakly correlated with peak VO2 (r = 0.25, p = 0.046) but not with VE/VCO2. In contrast, CPO at peak exercise was positively correlated with peak VO2 (r = 0.50, p < 0.001) and inversely correlated with VE/VCO2 (r=-0.40, p = 0.002). Moreover, CPO at peak exercise determined both peak VO2 (b = 0.50) and VE/VCO2 (β=-0.54) independently of LV ejection fraction and E/e" at peak exercise. During a median follow-up period of 1211 days, 12 cardiac events were observed. Each of reduced peak VO2 (hazard ratio 0.78, 95% confidence interval 0.66-0.90) and increased VE/VCO2 (hazard ratio 1.10, 95% confidence interval 1.02-1.18) was associated with worse clinical outcome. Conclusions: In patients with chronic heart failure, CPO during exercise was associated with prognosis of heart failure through the reduced exercise capacity and enhanced ventilatory response.